Ciało, gest, literatura - Gruszczyk, Tomasz (Humaniora. Czasopismo Internetowe, 2021)
As Maurice Merleau-Ponty wrote, the experience of the body, the somatic experience and the gesture as an act of expression bring into being both the sense of things that are being interacted with and the sense of existence of which the body is a vehicle. If so, then the verbal expression, creativity, literature – apart from the fact that it is (most often) a representation of things (and thoughts) that are already anchored in culture and create its universe – can be an individual event of a similar nature and course: becoming, creating, bringing out the subject-body in writing and in what’s being written. The works of Stanisław Czycz serve as an example of such literature-gesture. They have specific characteristics of autobiographical and autocreational writing, and also take up the problem of experiencing the body and corporeality. However, they are analyzed here as autoteleological work – as a gesture of a body that is being created and a body that is creating its own sense.